Functional and structural abnormalities of the skin microcirculation in hemodialysis patients - Maggie S El-Nahid; Ali M El-Ashmaoui (SpringerOpen, 2014)
Background The changes that occur at the level of the skin microvessels reflect changes at other microvessels including the cardiac microvessels. Several disease states seem to alter skin microvascular function and structure such as diabetes, hypertension, and hypercholesterolemia. Many of these disease states are frequently encountered in hemodialysis (Hdx) patients. The process of Hdx itself is also associated with vascular abnormalities. It was thus the aim of our study to examine the structure and function of skin microcirculation in Hdx patients. Materials and methods Sixty patients were examined: 20 patients on regular Hdx, younger than 60 years old, with no diabetes, hypertension, or hypercholesterolemia, 20 patients on regular hemodialysis with coexisting hypertension (Htn-Hdx), and 20 young healthy volunteers. The skin microcirculation was assessed using the laser Doppler fluxmetry and the capillaroscope. Results Results showed significant differences in the laser Doppler fluxmetry measurements between the Hdx group and the Htn-Hdx group compared with the control group, with no significant differences in the capillaroscope study. Conclusion The study of skin microcirculation in Hdx patients indicated the presence of functional abnormalities without significant structural changes.